Role of sleep duration and sleep-related problems in the metabolic syndrome among children and adolescents (2018)
Background: There is increasing recognition that sleep is a risk factor for metabolic syndrome (MetS). The aim of the present study was to analyze the relationship between self-reported sleep duration, sleep-related problems and the presence of MetS in children and adolescents from Bogotá, D.C., Colombia. Methods: This is a cross-sectional analysis from the FUPRECOL study (2014-15). Participants included 2779 (54.2% girls) youth from Bogota (Colombia). MetS was defined as the presence of ≥3 of the metabolic abnormalities (hyperglycemia, hypertriglyceridemia, low high-density lipoprotein cholesterol [HDL-c], hypertension, and increased waist circumference) according to the criteria of de Ferranti/Magge and colleges. Self-reported sleep duration and sleep-related problems were assessed with the BEARS questionnaire. Results: Logistic regression analysis showed that boys who meet recommended duration of sleep had a decreased risk of elevated blood glucose levels (Odds Ratio [OR] = 0.71, 95%CI [0.40-0.94]; p = 0.031) compared to boys who have short-long sleep duration. Also, compared to young without sleep problems, excessive sleepiness during the day was related to low HDL-c levels in boys (OR = 1.36, 95%CI [1.02-1.83]; p = 0.036) and high triglyceride levels in girls (OR = 1.28, 95%CI [1.01-1.63]; p = 0.045). Girls with irregular sleep patterns had decreased HDL-c levels (OR = 0.71, 95%CI [0.55-0.91]; p = 0.009). Conclusions: Recommended sleep duration was associated with a decreased risk of elevated fasting glucose levels in boys, and sleep problems was related to lower HDL-c in girls and higher triglyceride levels in boys. These findings suggested the clinical importance of improving sleep hygiene to reduce metabolic risk factors in children and adolescents. © 2018 The Author(s).